Kaposi's Sarcoma–Associated Herpesvirus Infection of Neurons in HIV-Positive Patients. (7th December 2016) - Tso, For Yue; Sawyer, Ashley; Kwon, Eun Hee; Mudenda, Victor; Langford, Dianne; Zhou, You; West, John; Wood, Charles
Abstract: Background: Kaposi's sarcoma–associated herpesvirus (KSHV) is the causative agent of Kaposi sarcoma (KS), one of the leading cancers in human immunodeficiency virus (HIV)–infected patients in Zambia. KSHV was detected in the human central nervous system (CNS) by polymerase chain reaction (PCR) analysis, but tissue location and cell tropism for KSHV infection has not been established. Given the neurotropism exhibited by other herpesviruses and the frequent coinfection of HIV-positive individuals by KSHV, we sought to determine whether the central nervous system (CNS) can be infected by KSHV in HIV-positive Zambian individuals. Methods: Postmortem brain tissue specimens were collected from individuals coinfected with KSHV and HIV. PCR and Southern blots were performed on DNA extracted from the brain tissue specimens to verify KSHV infection. Immunohistochemical analysis and immunofluorescent microscopy were used to localize and identify KSHV-infected cells. Tropism was further established by in vitro infection of primary human neurons with rKSHV.219. Results: KSHV DNA was detected in the CNS from 4 of 11 HIV-positive individuals. Immunohistochemical analysis and immunofluorescent microscopy demonstrated that KSHV infected neurons and oligodendrocytes in parenchymal brain tissues. KSHV infection of neurons was confirmed by in vitro infection of primary human neurons with rKSHV.219. Conclusion: Our study showed that KSHV infects human CNS-resident cells, primarily neurons, in HIV-positive Zambian individuals.